Efektifitas Penerapan E-Government Pada Dinas Kependudukan Dan Catatan Sipil Kabupaten Sragen Dalam Program Sistem Informasi Administrasi Kependudukan (SIAK) - Aris Setiawan; Rr Hermini S; D Ghulam Manar (Journal of Politic and Government Studies, 2013)
AbstractReasons of this paper is that the Population and Civil Registration Agency Sragen is one district in Indonesia which was awarded Best Of The Best e-Government Award 2007 from Warta Ekonomi in e-Government implementation. One implementation of e-Government in Sragen is application in SIAK2program. SIAK is a web-based information system that is based on the procedures and standards used specifically aimed at managing the administrative system in the field of population in order to achieve orderly administration and also help the officers to held in the population and civil registration service. Population Administration Information System in Sragen based on Sragen Local Regulation No. 10 of 2011 on the Implementation of Civil Affairs. The main guidelines for the application of SIAK regulated in Regulation No. 23 of 2006 on Population Administration and Government Regulation No. 37 of 2007 on the Implementation of Law No. 23 of 2006 concerning Population Administration. In addition, SIAK also regulated in Presidential Decree No. 88 of 2004 on Management of Population Administration.The purpose of this study is determine the effectiveness of the implementation of e-Government at the Civil Registration and Population Agency Regency Sragen in the Population Administration Information System (SIAK) program and constraints encountered in implementation. This study uses descriptive qualititative type of method in order to obtain a clear picture of the object under study and draw conclusions.The results shows that the application of SIAK program at Population and Civil Registration Agency Sragen is effective, visible, and run faster. But there are still this in dealing with human resources SIAK program, there are SIAK officers in districts thathave not been able to operate the program SIAK to the absence of training for operators SIAK..Keywords: e-Government, Effectiveness, Information Technology, SIAK